Criticism of Orientalist Critical Views Toward Hadith Studies - Qohin, Abd.; Kasiyati, Siti (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
This article discusses the orientalist views of the Prophet Muhammad's hadith. Discusses the differences in hadith studies in the West and in the East as well as views on the sanad al-hadith and the matn al-hadith. In addition, it also discusses the rebuttal of the Orientalist theory. The approach of this article uses the study of literature studies (Library Research) using qualitative-descriptive methods and approaches. The results of this study indicate that Orientalist views on the hadith are the same, namely criticizing the authenticity of the hadith in terms of both sanad, matn, and rawi. The subjectivity of Orientalists who at least keep their own missions to corner Islam behind the lens of orientalism, which is actually a neo-colonialism over the Eastern hemisphere, especially the Islamic region as their goal of studying the hadith. Disclaimers made by the hadith scholars such as Azami in order to destroy their theories based on depth research and justified scientifically.